Developing a Culture-Adequate Intercultural Competence Program for Indonesian Students - Panggabean, Hana; Murniati, Juliana (ANIMA Indonesian Psychological Journal, 2010)
Numerous challenges of Indonesian multicultural society (e.g., intergroup conflicts) indicate the needs for intercultural education. This study attempts to develop a culture-adequate learning pro- gram of intercultural competence for university students in Indonesia. A cultural adaptation of a German cultural-oriented training is conducted. The theoretical framework covers intercultural training, culture learning for students, and cross-cultural learning style of European and Asian stu- dents. Data collection includes expert interviews (N = 5) and focus group discussions of profes- sionals (N = 21). Achievement test, multicultural awareness scale and open ended questionnaire are delivered to 34 psychology students. Content analysis and descriptive statistics are applied. The customized module receives favourable response for its learning strategies and is considered beneficial for students’ multicultural development. The program increases cultural knowledge and cultural diversity awareness. Tantangan masyarakat majemuk Indonesia mengindikasikan kebutuhan pengembangan kompe- tensi mengelola keberbedaan secara sistematis. Studi ini berfokus pada penyusunan program pen- gembangan dengan mengadaptasi modul berorientasi budaya Jerman ke dalam konteks Indonesia. Untuk proses adaptasi ini dilakukan wawancara (N = 5) dan focus group discussion (N = 21). Hasil dari pendekatan kualitatif memberikan justifikasi akan kebutuhan program demikian di dunia kerja serta sejumlah kasus pertemuan budaya dalam konteks Indonesia untuk materi pembelajaran. Uji coba modul hasil adaptasi dilakukan pada mahasiswa (N = 34) dengan memberikan tes prestatif, skala multicultural diversity awareness, dan kuesioner terbuka. Hasil analisis memperlihatkan perubahan yang signifikan pada pengetahuan subjek sebelum dan sesudah mengikuti uji coba modul dan terjadi peningkatan kesadaran akan kemajemukan pada subjek. Subjek penelitian juga memberikan evaluasi positif terhadap modul dengan fokus utama pada manfaatnya dalam memberikan pemahaman akan kemajemukan dan pengembangan diri, serta metode belajar eksperiensial-induktif.